(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: A prospective, observational study in Dhaka Medical College Hospital was carried out to assess the efficacy of loop electrosurgical excision procedure (LEEP) of the transformation zone of cervix as an outpatient procedure as diagnostic and therapeutic purpose during visit of patients with the report of CIN II or CIN III on histopathology. Method: One hundred women over a period of one year from 1st January to 31st December 2011 were treated with LEEP as an outpatient procedure. Among these women 63 patients were CIN II and 37 patients were CIN III on histopathology report. LEEP were done under local anaesthesia. All patients were followed up for one year with colposcopy and also histology where appropriate. Results: In all cases, the specimens obtained were adequate for histopathological assessment and in 98 (98%) cases the lesion had been completely excised. Two cases of CIN III required a second excision. One patient needed cervical sutures to achieve haemostasis following the excision. One patient was admitted in the hospital with primary haemorrhage. Two patients were admitted with secondary haemorrhage. Conclusion: LEEP under local anaesthesia is an effective technique. It enables the treatment of patients with cervical intraepithelial neaplasia and exclusion of invasive cancer in a subsequent visit. Thus adequate tissue is made available for accurate diagnosis, thereby improving the accuracy of treatment. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(1) : 5-8